Wyzwania kryzysu zadłużenia strefy euro dla poszukiwania nowej roli Niemiec w Unii Europejskiej w XX wieku - CZIOMER, ERHARD (Rocznik Integracji Europejskiej, 2012)
The paper tries to present the role and importance of Germany for overcoming the debt crisis and searching for a new role to play in the EU. It consists of three parts, which concentrate on an analysis of the following issues: 1) the origin, nature and implications of the eurozone crisis for Germany, 2) the role of Germany in the efforts to overcome the eurozone debt crisis, 3) general challenges the eurozone debt crisis poses for Germany in its search for a new role in the EU. The fundamental thesis of the paper is that, owing to its enormous financial and economic potential, Germany became a key actor in the efforts to rescue the eurozone in 2010–2012. However, due to complex internal conditions, excessive promotion of German interests in European politics by the CDU/CSU/FDP government and Chancellor Merkel’s prolonged procrastination over necessary and long-awaited Community decisions prevented Germany from assuming the fully-approved political leadership of the EU during the eurozone crisis at the turn of the first decade of the twenty-first century.